2021
DOI: 10.7759/cureus.20597
|View full text |Cite
|
Sign up to set email alerts
|

Which Fibers of the Medial Collateral Ligament (MCL) Should Be Released in the Pie Crust Technique Applied During Knee Arthroscopy: Superficial MCL or Deep MCL?

Abstract: Background Knee arthroscopy is the most common surgery performed to treat meniscal injuries. The pie crust (PC) technique is applied during knee arthroscopy to increase joint vision of the medial femorotibial compartment and reduce the risk of iatrogenic damage. Medial collateral ligament (MCL) release is applied in the PC technique. Currently, there are no studies directly comparing the release of the superficial MCL (sMCL) or deep MCL (dMCL) when applied during the PC technique. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This potentially indicates a lack of education and scientific understanding of the anatomy or method of release. The evidence is limited, however, a recent study found no radiological or functional difference when releasing the deep versus superficial MCL 9 . Current techniques could be improved with better anatomical understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potentially indicates a lack of education and scientific understanding of the anatomy or method of release. The evidence is limited, however, a recent study found no radiological or functional difference when releasing the deep versus superficial MCL 9 . Current techniques could be improved with better anatomical understanding.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is limited, however, a recent study found no radiological or functional difference when releasing the deep versus superficial MCL. 9 Current techniques could be improved with better anatomical understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Studies ( 1 , 2 ) have examined changes in the medial joint space and reported varying degrees of medial space increase in the immediate postoperative period, which tend to stabilize over time. The use of postoperative knee braces has been recommended in some cases to mitigate the risk of instability, although it is not universally required ( 1 , 8 , 9 ). Clinical results suggest that the decision to use a brace postoperatively should be individualized and based on the patient’s condition and surgeon’s preference ( 8 , 9 ).…”
Section: Step-by-step Descriptionmentioning
confidence: 99%
“…The use of postoperative knee braces has been recommended in some cases to mitigate the risk of instability, although it is not universally required ( 1 , 8 , 9 ). Clinical results suggest that the decision to use a brace postoperatively should be individualized and based on the patient’s condition and surgeon’s preference ( 8 , 9 ). Fortunately, many patients experience favorable postoperative outcomes, including improved functional scores ( 8 , 9 ).…”
Section: Step-by-step Descriptionmentioning
confidence: 99%
See 1 more Smart Citation